2016
DOI: 10.1007/s11883-016-0566-5
|View full text |Cite
|
Sign up to set email alerts
|

Troponin in Cardiovascular Disease Prevention: Updates and Future Direction

Abstract: Cardiac troponin has been well described as the preferred biomarker for diagnosis of myocardial infarction due to the high sensitivity and specificity for myocardial injury. Numerous other conditions apart from acute coronary syndrome can also lead to small elevations in troponin levels. However, the use of cTn as prognostic biomarker for the primary assessment of cardiovascular risk in asymptomatic patient has only recently been described. And with the development of newer generations of high-sensitivity card… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 70 publications
0
28
0
Order By: Relevance
“…The repeated administration of TRB reduced the levels of troponin I in serum (Figure B). Troponin I, one of the three subunits that form troponin present in striated muscle, is used as the biomarker for diagnosis myocardial injury . It is reported that serum troponin I level of SHR is higher than normotensive strain such as WKY, SD, and Wistar rats .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The repeated administration of TRB reduced the levels of troponin I in serum (Figure B). Troponin I, one of the three subunits that form troponin present in striated muscle, is used as the biomarker for diagnosis myocardial injury . It is reported that serum troponin I level of SHR is higher than normotensive strain such as WKY, SD, and Wistar rats .…”
Section: Discussionmentioning
confidence: 99%
“…Troponin I, one of the three subunits that form troponin present in striated muscle, is used as the biomarker for diagnosis myocardial injury. [27,28] It is reported that serum troponin I level of SHR is higher than normotensive strain such as WKY, SD, and Wistar rats. [29] It was also reported that ACE inhibitors reduced troponin I in CVD patients with non-STelevation myocardial infarction, and cardiac events in high-risk CVD patients.…”
Section: Discussionmentioning
confidence: 99%
“…AICAR treatment attenuated this inflammatory response, but the effect was less prominent in the mature mice than the young group. On the contrary, levels of the placental growth factor PIGF2, an angiogenic factor (25), CXCL16, a chemokine involved in neutrophil recruitment (26) and the classical cardiac biomarkers troponin-I and troponin-T (27) were not different among vehicle or AICAR-treated groups of either age. Taken together, these data, therefore, suggest an important contribution of the inflammatory response in mature animals.…”
Section: Discussionmentioning
confidence: 99%
“…1 There is a common interest in identifying sub-clinical disease before serious manifestation with increased morbidity and mortality. 3 Recent population studies report an association between a single measurement of elevated hs-cTn value with heart failure (HF), coronary artery disease (CAD) and all-cause mortality. With the advent of cardiac troponin high-sensitivity (hs-cTn) assays, it is now possible to measure troponin values in majority of healthy individuals.…”
Section: Introductionmentioning
confidence: 99%